Extraction and bioprocessing with supercritical fluids - Coelho, Jose (2020)
Supercritical fluid (SCF) technologies have emerged as a real alternative to various natural product extraction processes and pharmaceutical production to obtain micronized particles, coprecipitates, nanocomposite polymer structures and liposomes, in addition to other increasingly larger applications described in literature. In the present work, a brief literature review of the application of supercritical fluid extraction (SFE) is presented. This is evidenced by several publications and patents, contributions from several countries and the increase of industries around the world dedicated to this technique. Next, we aim to focus the analysis of SFE on a review of the literature applied to microalgae as a substitute primitive feedstock due to its high growth rate, valuable biologically active lipophilic substances, and photosynthetic efficiency without competition with food sources or needs of arable lands. We finally discussing an SCF bioprocess with a very new perspective for liposome production focalized on its potential at industrial scale.